Redescription of Microterys chalcosotmus (Dalman) (Hymenoptera: Chalcidoidea: Encyrtidae), a parasitoid associated with Phenacoccus aceris (Signoret) (Hemiptera: Pseudococcidae) and Kermes spp. (Hemiptera: Kermesidae), with comments on its host relationship. Issue 19 (18th May 2020) - Guerrieri, Emilio; Formisano, Giorgio; Noyes, John S.
ABSTRACT: This paper is a contribution to the characterisation by an integrated approach of the species Microterys chalcostomus (Dalman), a parasitoid of mealybugs and apparently a predator of kermesid eggs. Until now, the species, whose type is in good condition, could be identified only by the meagre original description by Dalman and subsequent notes by Graham. Nonetheless, it appears to be extremely common in Europe, hence the need for a thorough morphological and molecular characterisation. Systematic notes on closely related species of Microterys parasitoids of mealybugs are included.